Perinatal And Maternal Outcomes of Oligohydraminos In Third Trimester Pregnancy: A cross sectional comparative study At Felegehiwot Comprehensive Specialized Hospital And Tibebe Ghion Specialized Hospital , Bahirdar, North West Ethiopia,2019 - Yimam, Yismaw (Ethiopian Journal of Reproductive Health, 2020)
ABSTRACT INTRODUCTION; Oligohydraminos is most commonly defined as an amniotic fluid index (AFI) ? 5 cm. It is considered a risk factor for adverse fetal and maternal outcome. Objective: To compare perinatal and maternal outcomes among oligohydraminos and non oligohydraminos pregnancies. Methods: A cross sectional comparative study with prospective facility based follow up study was done. The sample size is calculated to be 51 and 102, 1:2 for oligohydraminos and non-oligohydraminos respectively. The collected data was cleaned, coded and entered into EPI- data version 3.1, and exported in to a SPSS Version 23.0 for analysis. Strength of association between the explanatory variables and outcome variables was described using odds ratio at 95% CI, and P value less than 0.05, were considered to declare statistical significance. The results presented in tables and charts. Results: The Cesarean delivery rate in women with oligohydraminos was 61%, compared to 22% in non oligohydraminos group, statistically significant (P < 0.001). 5-min Apgar score <7 was observed in 20 (40%) neonates in oligohydraminos (p = 0.002) and 16(15%) in non-oligohydramnios, it is statistically significant. NICU admission was required for 14 (27 %) versus 11(10 %) babies in oligohydraminos and non oligohydraminos, respectively; this is found to be statistically significant (p = 0.011). The risk of adverse neonatal outcome was not related to GA at delivery, C/S, parity, age and antenatal follow up. Conclusions: Oligohydraminos has a significant correlation with adverse perinatal and maternal outcome. ABSTRACT INTRODUCTION; Oligohydraminos is most commonly defined as an amniotic fluid index (AFI) ? 5 cm. It is considered a risk factor for adverse fetal and maternal outcome. Objective: To compare perinatal and maternal outcomes among oligohydraminos and non oligohydraminos pregnancies. Methods: A cross sectional comparative study with prospective facility based follow up study was done. The sample size is calculated to be 51 and 102, 1:2 for oligohydraminos and non-oligohydraminos respectively. The collected data was cleaned, coded and entered into EPI- data version 3.1, and exported in to a SPSS Version 23.0 for analysis. Strength of association between the explanatory variables and outcome variables was described using odds ratio at 95% CI, and P value less than 0.05, were considered to declare statistical significance. The results presented in tables and charts. Results: The Cesarean delivery rate in women with oligohydraminos was 61%, compared to 22% in non oligohydraminos group, statistically significant (P < 0.001). 5-min Apgar score <7 was observed in 20 (40%) neonates in oligohydraminos (p = 0.002) and 16(15%) in non-oligohydramnios, it is statistically significant. NICU admission was required for 14 (27 %) versus 11(10 %) babies in oligohydraminos and non oligohydraminos, respectively; this is found to be statistically significant (p = 0.011). The risk of adverse neonatal outcome was not related to GA at delivery, C/S, parity, age and antenatal follow up. Conclusions: Oligohydraminos has a significant correlation with adverse perinatal and maternal outcome. ABSTRACT INTRODUCTION; Oligohydraminos is most commonly defined as an amniotic fluid index (AFI) ? 5 cm. It is considered a risk factor for adverse fetal and maternal outcome. Objective: To compare perinatal and maternal outcomes among oligohydraminos and non oligohydraminos pregnancies. Methods: A cross sectional comparative study with prospective facility based follow up study was done. The sample size is calculated to be 51 and 102, 1:2 for oligohydraminos and non-oligohydraminos respectively. The collected data was cleaned, coded and entered into EPI- data version 3.1, and exported in to a SPSS Version 23.0 for analysis. Strength of association between the explanatory variables and outcome variables was described using odds ratio at 95% CI, and P value less than 0.05, were considered to declare statistical significance. The results presented in tables and charts. Results: The Cesarean delivery rate in women with oligohydraminos was 61%, compared to 22% in non oligohydraminos group, statistically significant (P < 0.001). 5-min Apgar score <7 was observed in 20 (40%) neonates in oligohydraminos (p = 0.002) and 16(15%) in non-oligohydramnios, it is statistically significant. NICU admission was required for 14 (27 %) versus 11(10 %) babies in oligohydraminos and non oligohydraminos, respectively; this is found to be statistically significant (p = 0.011). The risk of adverse neonatal outcome was not related to GA at delivery, C/S, parity, age and antenatal follow up. Conclusions: Oligohydraminos has a significant correlation with adverse perinatal and maternal outcome. ABSTRACT INTRODUCTION; Oligohydraminos is most commonly defined as an amniotic fluid index (AFI) ? 5 cm. It is considered a risk factor for adverse fetal and maternal outcome. Objective: To compare perinatal and maternal outcomes among oligohydraminos and non oligohydraminos pregnancies. Methods: A cross sectional comparative study with prospective facility based follow up study was done. The sample size is calculated to be 51 and 102, 1:2 for oligohydraminos and non-oligohydraminos respectively. The collected data was cleaned, coded and entered into EPI- data version 3.1, and exported in to a SPSS Version 23.0 for analysis. Strength of association between the explanatory variables and outcome variables was described using odds ratio at 95% CI, and P value less than 0.05, were considered to declare statistical significance. The results presented in tables and charts. Results: The Cesarean delivery rate in women with oligohydraminos was 61%, compared to 22% in non oligohydraminos group, statistically significant (P < 0.001). 5-min Apgar score <7 was observed in 20 (40%) neonates in oligohydraminos (p = 0.002) and 16(15%) in non-oligohydramnios, it is statistically significant. NICU admission was required for 14 (27 %) versus 11(10 %) babies in oligohydraminos and non oligohydraminos, respectively; this is found to be statistically significant (p = 0.011). The risk of adverse neonatal outcome was not related to GA at delivery, C/S, parity, age and antenatal follow up. Conclusions: Oligohydraminos has a significant correlation with adverse perinatal and maternal outcome. ABSTRACT INTRODUCTION; Oligohydraminos is most commonly defined as an amniotic fluid index (AFI) ? 5 cm. It is considered a risk factor for adverse fetal and maternal outcome. Objective: To compare perinatal and maternal outcomes among oligohydraminos and non oligohydraminos pregnancies. Methods: A cross sectional comparative study with prospective facility based follow up study was done. The sample size is calculated to be 51 and 102, 1:2 for oligohydraminos and non-oligohydraminos respectively. The collected data was cleaned, coded and entered into EPI- data version 3.1, and exported in to a SPSS Version 23.0 for analysis. Strength of association between the explanatory variables and outcome variables was described using odds ratio at 95% CI, and P value less than 0.05, were considered to declare statistical significance. The results presented in tables and charts. Results: The Cesarean delivery rate in women with oligohydraminos was 61%, compared to 22% in non oligohydraminos group, statistically significant (P < 0.001). 5-min Apgar score <7 was observed in 20 (40%) neonates in oligohydraminos (p = 0.002) and 16(15%) in non-oligohydramnios, it is statistically significant. NICU admission was required for 14 (27 %) versus 11(10 %) babies in oligohydraminos and non oligohydraminos, respectively; this is found to be statistically significant (p = 0.011). The risk of adverse neonatal outcome was not related to GA at delivery, C/S, parity, age and antenatal follow up. Conclusions: Oligohydraminos has a significant correlation with adverse perinatal and maternal outcome.